Reduction of blooming artifacts in cardiac CT images by blind deconvolution and anisotropic diffusion filtering (2015)
Even though CT is an imaging technique that offers high quality images, limitations on its spatial resolution cause blurring in small objects with high contrast. This phenomenon is known as blooming artifact and affects cardiac images with small calcifications and stents. This paper describes an approach to reduce the blooming artifact and improve resolution in cardiac images using blind deconvolution and anisotropic diffusion filtering. Deconvolution increases resolution but reduces signal-to-noise ratio, and the anisotropic diffusion filter counteracts this effect without affecting the edges in the image. © 2015 SPIE.